(untitled) (Forum Theologicum Sardicense, 2025)
St. Gregory Palamas developed the theme of the apodeictic method in many of his works. Indeed, he developed it extensively in two epistolary treatises to Akindynus and in two to Barlaam. According to the saint, theology is not a theoretical art, but has a positive character and is an experienced knowledge. Not only because the creatures themselves venerate and glorify God; not only because of human nature itself and the all-harmonious universe, but also because of the very experience of the saints, of God‘s friends, who, after being purified, saw God appearing to the pure and worthy in heart.